Downconversion Materials for Perovskite Solar Cells. Issue 8 (9th June 2022) - Datt, Ram; Bishnoi, Swati; Hughes, Declan; Mahajan, Prerna; Singh, Anoop; Gupta, Ramashanker; Arya, Sandeep; Gupta, Vinay; Tsoi, Wing Chung
Abstract : Perovskite solar cells (PSCs) have made game‐changing progress in the last decade and reached a power conversion efficiency (PCE) of up to 25%. Furthermore, the development of material chemistry, structure design, active layer composition, process engineering, etc. has contributed to improving PSCs' stability. The significant PCE losses experienced by PSCs are related to spectral mismatch between the incident solar spectra and absorption range of the active layer, which thereby limits the PCE. Besides PSCs' performance, the photoinduced degradation is also a major concern. Recently, lanthanide (rare‐earth) and nonlanthanide‐based downconversion (DC) materials have been introduced to resolve these spectral mismatch losses as well as reduce the photoinduced degradation. The DC materials improve the photovoltaic performance by converting ultraviolet (UV) light to visible, also providing UV shielding, and thus contribute to increasing the efficiency as well as stability of PSCs. Moreover, the Shockley–Queisser efficiency limit of the solar cell can be crossed with the help of DC materials. In this review, the importance, processing, and the reported DC materials for PSCs are thoroughly discussed. Furthermore, the development of DC materials and their impact on PSCs' performance and stability, along with their future perspectives, are focused. Abstract : The review focuses on the benefits of downconversion (DC) materials in improving the perovskite solar cells' (PSCs) performance and photostability. It contains a conclusive analysis of the reported two categories called the lanthanides and nonlanthanides‐based DC materials for PSCs. It also suggests that the DC materials‐based PSCs devices can work well under ultraviolet‐rich environments such as space.